Pathogenic Bacillus cereus isolated from bovine - Analysis of Biofilm - Chen Yun jiao; Jia Wei juan; Meng Qing lei; Wang Xue li (Acta Scientiae Veterinariae, 2023)
Background: Bacillus cereus is a gram-positive bacterium, which is widely distributed and has certain pathogenicity. B. cereus can cause food poisoning in animals and humans, and occasionally causes subcutaneous abscess, eye infection, bacteremia and other diseases. Our team has identified a strain of B. cereus containing hemolysin BL (HBL), non-hemolysin enterotoxin (Nhe), cytotoxin K (CytK) and enterotoxin FM (entFM), and successfully constructed the detection method of Nhe gene RPA-LF. Also, B. cereus can adhere to living and non-living surfaces and aggregate to form biofilms. This paper aims to provide data support for the elimination and control of Bacillus cereus biofilm. Materials, Methods & Results: In study, crystal violet staining and XTT detracting method were used to determine the forming ability, metabolic activity and some biological characteristics of biofilms, and microdilution method was used to determine the minimum inhibitory concentration of 5 kinds of Traditional Chinese medicine extracts and 5 kinds of antibiotics on biofilms. The effects of Bacillus cereus biofilm formation on the pathogenicity of different organs of animals were observed by inoculation test and pathological section. The results showed that the bacteria had strong ability to form biofilms and compact structure. The optimal temperature was 37℃; optimal pH was 7; 0.5% NaCl; 0.5%-3% glucose; and 200% TSB medium could promote the formation of biofilms. The minimum inhibitory concentration of baicalin, berberine, panichololide, emodin and sodium houttuynitin on biofilms were 128 μg/mL, 256 μg/mL, 256 μg/mL, 256 μg/mL and 512 μg/mL, respectively. The minimum inhibitory membrane concentrations of azithromycin, ampicillin, gentamicin, en-rofloxacin and flufenicol for biofilm were 32 μg/mL, 64 μg/mL, 64 μg/mL, 64 μg/mL and 128 μg/mL, respectively. The bacterium can make healthy mice infected and die, and cause different degrees of organ damage. The changes of nutrients and growth environment will lead to changes in the growth of biofilm. Different drugs had different inhibitory effects on biofilms, among which azithromycin and baicalin were the best. Discussion: Bacillus cereus, as a toxin-producing conditioned pathogen, has attracted great attention in various industries, because the bacterium can produce spores and biofilms in adverse environments, improving its ability to survive high temperature, drying and antibiotics. The formation of B. cereus biofilms is currently a topic of great concern in medicine, the environment and food microbiology as it can cause serious public health problems, so infections caused by biofilms need to be treated at an early stage. At present, there is no best way to detect and treat biofilms in the body, so early diagnosis and treatment become particularly difficult, and there is a need to develop more effective methods to remove biofilms at the root to reduce the harm caused by biofilms. In this study, the biofilm forming ability of bovines lethal B. cereus was identified, and its growth characteristics under different culture conditions were studied, and the inhibition and clearance effects of Chinese medicine extracts and antibiotics on Bacillus cereus were respectively explored, in order to lay a theoretical foundation for the subsequent study of its formation mechanism and comprehensive prevention and control of the disease. Keywords: Bacillus cereus, biological membrane, biological characteristics, suppression and clearance.